2002
DOI: 10.1183/09031936.02.00295502
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation for acute respiratory failure

Abstract: Noninvasive ventilation (NIV) has emerged as a significant advance in the management of respiratory failure. There is now a wide body of prospective randomized-controlled trial data to support its use, particularly in the management of patients with acute or respiratory failure due to exacerbations of chronic obstructive pulmonary disease (COPD). Its successful application results in a more rapid resolution of the physiological derangements, reduces the need for intubation and, in larger studies, improves surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 67 publications
(74 reference statements)
0
32
0
5
Order By: Relevance
“…This may explain why baseline pH was a poorer discriminant in the patient population now referred for NIV. In contrast, the initial respiratory rate was a good measure of treatment response, as has been seen elsewhere 1 2 5 24 25. A higher RR may reflect asynchrony of the patient and the ventilator, but it may also be a marker of a greater intrinsic respiratory load promoting a shortened inspiratory time and more hypercapnia 26 27.…”
Section: Discussionmentioning
confidence: 77%
“…This may explain why baseline pH was a poorer discriminant in the patient population now referred for NIV. In contrast, the initial respiratory rate was a good measure of treatment response, as has been seen elsewhere 1 2 5 24 25. A higher RR may reflect asynchrony of the patient and the ventilator, but it may also be a marker of a greater intrinsic respiratory load promoting a shortened inspiratory time and more hypercapnia 26 27.…”
Section: Discussionmentioning
confidence: 77%
“…The increase in patient mortality did not exceed what would be predicted from SAPS II data despite the increasing use of NIV, suggesting that NIV is not associated with impaired prognosis in these patients. Indeed, it is now well known that, in patients with hypercapnic respiratory failure, NIV improves outcomes, especially survival, by reducing the need for intubation and the prevalence of related complications (23)(24)(25). In the nineties, it was shown that the use of NIV for AECOPD had changed over time (26).…”
Section: Trends Over Timementioning
confidence: 98%
“…The first-line treatment of patients with acute respiratory failure (ARF) is mechanical ventilation either with positive or negative pressure, invasively or noninvasively [1]. A great deal of clinical research has shown that non-invasive ventilation (NIV), is a valuable form of treatment for ARF.…”
Section: Introductionmentioning
confidence: 99%